2016
DOI: 10.1080/0284186x.2016.1250945
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a child’s cancer disease on parents’ everyday life: a longitudinal study from Sweden

Abstract: Background: A child's cancer disease may disrupt the daily life of the affected family for a long period. The aim was to describe restrictions on parents' leisure activities and work/studies during and after the child's treatment. Methods: This study used data from a cohort of mothers and fathers (n ¼ 246) of children diagnosed with cancer. Data was collected five times from two months after diagnosis to one year after end of treatment. Reports of restrictions were evaluated over time, between mothers and fath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 21 publications
2
39
0
6
Order By: Relevance
“…However, two studies from Australia and the United Kingdom observed that mothers were less likely to reduce work hours compared with fathers. Most work disruptions occurred shortly after diagnosis and attenuated within 1 year . However, studies from Sweden and Switzerland identified higher unemployment among mothers even many years after diagnosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, two studies from Australia and the United Kingdom observed that mothers were less likely to reduce work hours compared with fathers. Most work disruptions occurred shortly after diagnosis and attenuated within 1 year . However, studies from Sweden and Switzerland identified higher unemployment among mothers even many years after diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 3359 articles through literature searches and included 35 articles, reporting on 29 individual studies (Figure ). Thirteen (37%) studies were conducted in Europe, 16 (46%) in North America/Australia, and six (17%) in Asia/Africa (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that receiving a diagnosis of NF1 may be as difficult as receiving a cancer diagnosis. In previous Swedish studies describing PTSD in parents of children diagnosed with cancer, Hovén et al (6) demonstrated that approximately half of them presented PTSD (PTSD Checklist-Civilian version was used) 4 months after diagnosis, whereas 19% of the mothers and 8% of the fathers still presented ongoing symptoms 5 years after cancer treatment (7). Hence, even if PTSD is less frequent and less severe over time, it is important to know that it can continue for a few years in some parents, and doctors must be able to detect the symptoms and suggest psychotherapeutic intervention, if necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of cancer cytopathological features, it is well documented that children with cancer experience various upsetting symptoms related to disease process or treatment modality (Rodgers et al, 2013). Satisfactory relief of these distressing symptoms is an imperative goal for patients, parents and practitioners during treatment for cancer (Miller et al, 2011;Rodgers et al, 2016;Hovén et al, 2017). Not only are these upsetting symptoms key contributors to decreased perception of quality of life, disability to function and disease-related interference with daily activities, but they may also disturb treatment process and impact treatment efficacy (Arslan et al, 2013;Baggott et al, 2014).…”
Section: Introductionmentioning
confidence: 99%